Anti-aging efficacy of solid-state fermented ginseng with Aspergillus cristatus and its active metabolites - Park, Sang Cheol; Ji, Yura; Ryu, Jeoungjin; Kyung, Seoyeon; Kim, Minji; Kang, Seunghyun; Jang, Young Pyo (Frontiers in Molecular Biosciences, 2022)
Aspergillus cristatus is a beneficial fungus of microbial fermented teas such as China's Fuzhuan brick tea and Pu-erh tea, and is commonly called golden flower fungus (GFF) because its cleistothecium has a yellow millet or sand grain shape. Since natural materials fermented with GFF exhibit various physiological activities, a new active cosmeceutical ingredient was developed by solid-state fermentation of ginseng, a famous active material for healthy skin, with GFF. The extract of solid-state fermented ginseng with GFF (GFFG) exhibited potent anti-aging efficacy on the skin such as the increase of hyaluronic acid synthesis, aquaporin expression, and mRNA level of filaggrin in HaCaT keratinocyte. GFFG also inhibited the expression of MMP-1 increased by TNF-α in human dermal fibroblast. Sophisticated chromatographic and spectroscopic studies have elucidated isodihydroauroglaucin and flavoglaucin as the metabolites which were not present in ginseng extract nor GFF extract alone. Bioassay of these metabolites revealed that these compounds were part of active principles of GFFG. These results suggest that GFFG would be a potential active ingredient in anti-aging cosmeceutical products.